Garlic, green tea and turmeric extracts-mediated green synthesis of silver nanoparticles: Phytochemical, antioxidant and in vitro cytotoxicity studies - Arumai Selvan, D.; Mahendiran, D.; Senthil Kumar, R.; Kalilur Rahiman, A. (Journal of photochemistry and photobiology. B, Biology, 2018)
Phyto-synthesis of silver nanoparticles (AgNPs) was achieved using aqueous garlic, green tea and turmeric extracts, and characterized by different spectroscopic techniques. Phytochemical analysis revealed the presence of rich amount of biochemicals in these extracts, which serve as reducing and capping agents for converting silver nitrate into AgNPs. FT IR spectroscopy confirmed the role of biomolecules in the bioreduction and efficient stabilization of AgNPs. UV–Vis DRS spectra showed a band around 450 nm characteristics of AgNPs. XRD patterns revealed the crystalline nature of the synthesized AgNPs with fcc structure. SEM and TEM analysis revealed the spherical shape of the synthesized AgNPs with an average particle size of 8 nm. EDX analysis confirmed the purity of the synthesized AgNPs with a strong signal at 3.2 keV. The antioxidant activity was assessed by ABTS, DPPH, p-NDA, H2O2 and DMSO scavenging assays, in which the AgNPs synthesized using green method showed remarkable activity with respect to the standard antioxidants ascorbic acid and rutin. In vitro cytotoxicity activity was tested on four cancer cell lines such as human breast adenocarcinoma (MCF-7), cervical (HeLa), epithelioma (Hep-2) and lung (A549) along with one normal human dermal fibroblasts (NHDF) cell line. The AgNPs synthesized using turmeric extract exhibits excellent antioxidant and cytotoxicity activity compared to that synthesized using other extracts. [Display omitted] •We report green extracts-mediated phytosynthesis of AgNPs.•XRD patterns confirmed the face centered cubic (fcc) structure of AgNPs.•SEM and TEM analysis confirmed the morphology and size of the AgNPs.•In vitro antioxidant activity was tested by five different assays.•Turmeric extract mediated AgNPs exhibit higher biological activity.